Beastly bones - Ritter, William, 1984- (Ritter, William, 1984- Jackaby series., 2016)
In the late 1800s, in New England, Abigail Rook and her employer, private detective R. F. Jackaby, are the people to call when paranormal phenomenon occurs. When the owner of a species of shape-shifters disguised at kittens is found murdered and an unidentified beast begins attacking people and animals in a nearby town, Rook and Jackaby find themselves on the trial of a monster, a thief, and a murderer.